Defending the Role of Formal Education in South Africa: A Theoretical and Argumentative Perspective on Reform - Samuel Ntsanwisi (Educational Considerations, 2025)
This article critically examines the ongoing public debate about the relevance of the formal education system in South Africa. Critics argue that formal education is outdated, ineffective in addressing unemployment, and disconnected from market needs. Using Human Capital Theory as a framework, this paper challenges these claims and argues that the education system is not inherently flawed but requires targeted reforms to better serve societal and economic demands. Through a comprehensive analysis of existing literature, this study highlights the role of education in skill development, economic growth, and social mobility. It also addresses criticisms by advocating for the integration of vocational training, digital transformation, and curriculum adjustments to align with the Fourth and Fifth Industrial Revolutions. The paper concludes with recommendations for policy adjustments to enhance education's responsiveness to evolving market and societal needs.
Keywords: Education System; Criticism; Relevance; Skills Development; South Africa